Altered Gut Microbiome in Parkinson’s Disease and the Influence of Lipopolysaccharide in a Human α-Synuclein Over-Expressing Mouse Model - Gorecki, Anastazja M.; Preskey, Leah; Bakeberg, Megan C.; Kenna, Jade E.; Gildenhuys, Christi; MacDougall, Gabriella; Dunlop, Sarah A.; Mastaglia, Frank L.; Akkari, P. Anthony; Koengten, Frank; Anderton, Ryan S. (Frontiers in Neuroscience, 2019)
The interaction between the gut microbiota and alpha-synuclein (Syn) aggregation in Parkinson’s disease (PD) is receiving increasing attention. The objective of this study was to investigate gut microbiota, and effects of an inflammatory lipopolysaccharide (LPS) trigger in a human Syn over-expressing mouse model of PD (Thy1-αSyn). Stool samples from patients with confirmed PD and Thy1-Syn mice were analysed using 16S ribosomal RNA sequencing. Compared to healthy controls, the relative abundance of mucin-degrading Verrucomicrobiae and LPS-producing Gammaproteobacteria were greater in PD patients. In mice, the abundance of Gammaproteobacteria was negligible in both Thy1-αSyn and wild-type (WT) animals, while Verrucomicrobiae were reduced in Thy1-αSyn mice. The effect of LPS on intestinal barrier function was investigated in vitro using intestinal epithelial (IEC-6) cells, and in vivo via administration of LPS in drinking water to Thy1-Syn mice. Acute exposure to LPS in vitro resulted in a reduction and altered distribution of the tight junction markers ZO-1 and e-Cadherin around the cell membrane in IEC-6 cells, as shown by immunohistochemistry. LPS administration in Thy1-Syn mice resulted in the emergence of early motor manifestations at 10 weeks, compared to untreated mice who were still asymptomatic at this age. This study reaffirms that an altered microbiome exists in patients with PD, and supports the notion of a proinflammatory gut microbiome environment as a trigger for PD pathogenesis.